Synchronization of General Cost Standards and Regional Unit Price Standards in Aceh’s Regional Financial Management - Parlindungan Harahap; Yanis Rinaldi; Sanusi Sanusi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Orderly, efficient, transparent, and accountable local financial management requires consistency between the General Cost Standards and the Regional Unit Price Standards as references in planning and implementing the Regional Revenue and Expenditure Budget (APBD). In practice, discrepancies between these standards still occur and may create legal and governance problems. This study aims to analyze the inconsistency between the General Cost Standards of the Regional Government in Aceh and the Regional Unit Price Standards, and to formulate synchronization efforts based on state financial law. The research uses a normative legal method with statutory, conceptual, and analytical approaches through qualitative analysis of primary and secondary legal materials. The findings show that inconsistencies between the two standards may constitute abuse of authority, as the General Cost Standards, as a subordinate norm, must not conflict with the higher-ranking Regional Unit Price Standards. These inconsistencies include exceeding cost limits and adding expenditure components not regulated in the Regional Unit Price Standards, as identified by the State Audit Agency (BPK). Synchronization can be achieved by strengthening legal review, optimizing facilitation of local legal products, applying evidence-based budgeting, and improving the capacity of local financial management officials.